2021
DOI: 10.14744/phd.2021.20981
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ambivalent Sexism to Menstrual Attitude in Nursing Students

Abstract: Hemşirelik öğrencilerinde çelişik duygulu cinsiyetçiliğin menstrüal tutuma etkisi M enstrüasyon, her sağlıklı kadın tarafından deneyimlenen normal fizyolojik bir süreçtir. [1] Menstrüasyon, çeşitli kültürlerde farklı şekillerde ifade edilebilmektedir. [2] Menstrüasyona ilişkin tutum ve inançlar, olumlu ya da olumsuz olabilmekle birlikte; olumsuz tutumun yaygın olduğu bildirilmektedir. Bu olumsuz tutumlar; utanma, rahatsız edici bulma, fiziksel -psikolojik olarak yük, engelleyici olarak görme, menstrüasyon döne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Articles on menstruation as an outcome found that in women, BS is associated with favorable attitudes toward menstruation (e.g., perceiving it as a natural, pleasant event; Aker et al, 2021; Marván et al, 2014) and favorable evaluations of premenstrual women (e.g., sensitive; Chrisler et al, 2014). Still, BS in women restricts them during menstruation, in that it predicted a set of prescriptions (e.g., taking hot showers) and proscriptions (e.g., not carrying heavy things) for menstruating women and the belief that menstruation keeps women from fully accomplishing their daily activities (Marván et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles on menstruation as an outcome found that in women, BS is associated with favorable attitudes toward menstruation (e.g., perceiving it as a natural, pleasant event; Aker et al, 2021; Marván et al, 2014) and favorable evaluations of premenstrual women (e.g., sensitive; Chrisler et al, 2014). Still, BS in women restricts them during menstruation, in that it predicted a set of prescriptions (e.g., taking hot showers) and proscriptions (e.g., not carrying heavy things) for menstruating women and the belief that menstruation keeps women from fully accomplishing their daily activities (Marván et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, HS in both men and women was associated with negative impressions of menstruating women (e.g., perceived as cold, lower on openness and conscientiousness; Chrisler et al, 2014; Forbes, Adams-Curtis, White, & Holmgren, 2003) and menopausal women (Chrisler et al, 2014). In women, HS predicted feelings of embarrassment about menstruation and rejection of it (Marván et al, 2014) and its effects (Aker et al, 2021), with ensuing potential health consequences (i.e., menstrual cycle-related symptoms; Marván et al, 2014).…”
Section: Resultsmentioning
confidence: 99%